Surrealismo y Umheimlich como conceptos para una comparación entre literatura y artes plásticas. El caso del diseñador Daniel Gil - José Manuel Ruiz Martínez (Impossibilia: Revista Internacional de Estudios Literarios, 2011)
The article explores book illustration as a privileged field for studying artistic interaction. Itproposes the concept of ‘surrealistic sensibility’, coined by Susan Sontag, and also the Freudian conceptof Umheimlich, as categories to understand how sometimes illustration is not only a mere visualtranslation of a written passage, but the process of transfer itself. The artist, instead of depicting, usestropes or symbols where meaning is explained by itself. Thus, rhetoric appears as a common fieldbetween literature and art. This idea is exemplified with the work of the Daniel Gil, an Spanish graphicdesigner.